Jejunal duplication in a 10-year-old boy presenting with generalized oedema and abdominal distension - Thitima Ngoenmak; Chaiyaporn Virochsangaroon; Krittaporn Phruksarudee; Napat Vimtrimate; Pattarawarin Wata (European Journal of Case Reports in Internal Medicine)
Background: Gastrointestinal tract duplications are rare congenital anomalies, with the jejunum being the second most common site after the ileum. These duplications can vary in size, location, and presence of ectopic mucosa, significantly impacting clinical presentation and often requiring surgical intervention. Case presentation: A 10-year-old Thai boy with haemoglobin (Hb) E trait and iron deficiency anaemia presented with significant oedema and abdominal distention. Laboratory investigations revealed isolated hypoalbuminemia. Imaging studies, including computed tomography (CT) scan, demonstrated a large, loculated, rim-enhancing air-fluid collection adjacent to the jejunum, along with mild dilatation and wall thickening of the affected jejunal loop. The patient underwent exploratory laparotomy, which included jejunal resection and jejunojejunal end-to-end anastomosis. Conclusion: Jejunal duplications are uncommon in children and can present diagnostic challenges, potentially leading to serious complications. This case underscores the importance of considering jejunal duplication in paediatric patients with unexplained abdominal distention and protein-losing enteropathy. Early recognition and timely surgical management are crucial to prevent severe complications and improve patient outcomes.